The Influence of Social Media Marketing, Brand Awareness, and Brand Love on Brand Loyalty in Customers of Azarine Skincare Products in the City of Surabaya - Lilyana Fransiska Sinaga; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Facial care, also known as skincare, has become an important part of people's lives, especially for women. The high level of awareness among the public to care for their facial skin so that it remains healthy and well-groomed has made the beauty industry experience rapid growth, especially in Indonesia. One of the local brands in the beauty industry in Indonesia is the Azarine brand. This research was conducted to find out what factors can influence customers in purchasing skincare products from the Azarine brand. The purpose of the research is to analyze the influence of social media marketing, brand awareness and brand love on brand loyalty among customers of Azarine skincare products in the city of Surabaya. This research uses quantitative research methods with associative descriptive research. The data collection technique is in the form of a survey using a questionnaire instrument. The sample used was160 respondents, who were taken from the research population, namely customers who have purchased Azarine skincare products who live in Surabaya City in 2024. The results of this research show that 1) Social Media Marketing, Brand Awareness, and Brand Love simultaneously influence Brand Loyalty for Azarine skincare products. 2) Social Media Marketing has a partial positive influence on Brand Loyalty for Azarine skincare products. 3) Brand Awareness has a partial positive influence on Brand Loyalty for Azarine skincare products. 4) Brand Love has a partial positive influence on Brand Loyalty for Azarine skincare products.